Groundwater Geochemistry of Neyveli Lignite Mine-Industrial Complex, Tamil Nadu, India and Its Suitability for Irrigation - Jayaprakash, M.; Ramasamy, Nagarajan; Muthusamy, S.; Gopal, V.; Arya, Viswam; Kalaivanan, P. (Cloud Publications, 2012)
This study was undertaken to assess the quality of groundwater for irrigation and level of trace metal concentration in the surface and groundwater bodies from Neyveli lignite mine-industrial complex which is located in Cuddalore district, Tamil Nadu, India. The hydrogeology of the Neyveli groundwater basin is extremely complex, consisting of a series of productive, confined aquifers below the lignite seam in both Mine I and II areas, while a semi-confined aquifer lies above the seam and occurs only in the Mine II area. The suitability of groundwater quality for agricultural purposes in and around Neyveli lignite mine-industrial complex was assessed by measuring physicochemical parameters, including major cation and anion compositions, pH, total dissolved solids, electrical conductivity, and trace metals. The results of the chemical analysis of the groundwater showed that concentrations of ions vary widely and the most prevalent water type is mixed CaNaHCO3, followed by other water types: mixed CaMgCl types and NaCl which is in relation with their interactions with the geological formations of the basin, dissolution of feldspars and chloride and bicarbonate minerals, and anthropogenic activities. The most dominant class is C1-S1, C2-S1 (85% PRM and 74% POM) in the study area, indicating that sodicity is very low and salinity is medium, and that these waters are suitable for irrigation in almost all soils.Based on sodium absorption ratio the groundwater of the study area is suitable for all types of crops and soil except for those crops sensitive to Na and based RSC values of the groundwater, considered safe. Based on the parameters such as TDS, EC, SO4, Cl and Wilcox diagram about 99% of samples are suitable for irrigation. The average concentration of trace metals (Fe, Mn, Cr, Zn, Pb, and Cu) in groundwater samples fall within the permissible limit, with the exception of Ni which is recorded higher than the permissible limit which may retard growth and metabolic activities while the groundwater used for irrigation.